2018
DOI: 10.12691/env-6-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Determination and Health Risk Assessment of Oyster Mushroom <i>Pleurotus tuberregium</i> (Fr.) Singer, Collected from Selected Markets in Imo State. NIGERIA

Abstract: Oyster mushroom Pleurotus tuberregium (Fr.)(Sing), Ǫsu, is a common mushroom which is used as food or medicine, more commonly as a soup thickener. This study investigated the presence of heavy metals (Zn, Pb, Ni, Cu) in wild samples of Pleurotus tuberregium sclerotia consumed within Imo state. The oyster mushrooms purchased from different markets from Imo State were mineralized with H 2 SO 4 and HNO 3 and analyzed using flame Atomic Absorption Spectrophotometer (AAS) Thermo Scientific model. The mean concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Similarly, the concentration of Cu in drinking water ranged from 0.176-1.176 mg/L, which was lower than the maximum permissible limit (2.0 mg/kg) [44]. On the other hand, the study found the concentration of Cu in an edible mushroom ranged from 51.19 to 53.56 mg/kg, higher than the maximum permitted limit (0.05 to 5 mg/kg) [50,52] and the mean concentration in fish accounted for 7.7 mg/kg, which was lower than the allowable limit (30.0 mg/kg) [53]. And also, the study found the mean concentration of Mn in fruit and vegetables ranged from 0.26-869 mg/kg that was lower than the guideline (500 mg/kg) [54].…”
Section: Heavy Metal Concentration In Foods and Drinking Watermentioning
confidence: 99%
“…Similarly, the concentration of Cu in drinking water ranged from 0.176-1.176 mg/L, which was lower than the maximum permissible limit (2.0 mg/kg) [44]. On the other hand, the study found the concentration of Cu in an edible mushroom ranged from 51.19 to 53.56 mg/kg, higher than the maximum permitted limit (0.05 to 5 mg/kg) [50,52] and the mean concentration in fish accounted for 7.7 mg/kg, which was lower than the allowable limit (30.0 mg/kg) [53]. And also, the study found the mean concentration of Mn in fruit and vegetables ranged from 0.26-869 mg/kg that was lower than the guideline (500 mg/kg) [54].…”
Section: Heavy Metal Concentration In Foods and Drinking Watermentioning
confidence: 99%